2011
DOI: 10.1007/s00249-011-0713-4
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc modulates copper coordination mode in prion protein octa-repeat subdomains

Abstract: In this work we present and analyse XAS measurements carried out on various portions of Prion-protein tetra-octa-repeat peptides in complexes with Cu(II) ions, both in the presence and in the absence of Zn(II). Because of the ability of the XAS technique to provide detailed local structural information, we are able to demonstrate that Zn acts by directly interacting with the peptide, in this way competing with Cu for binding with histidine. This finding suggests that metal binding competition can be important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 33 publications
1
39
1
Order By: Relevance
“…By performing a systematic XAS study of a set of samples in which Cu(II) at increasing concentrations was added to tetra-octarepeat–Zn(II) complexes, we showed that the metal–peptide coordination mode depends not only, as expected, on the relative concentrations of the metals but, by comparison with the old XAS measurement of Stellato et al (2011), that the order in which the two metal ions are added to metal–tetra-octarepeat complexes is also important. Indeed, not only is Zn(II) unable to completely remove octarepeat-bound Cu(II) ions (as was already made clear by Stellato et al 2011) but, as we prove here, the opposite is also true, i.e. Cu(II) modifies the mode of Zn(II) coordination by partly displacing it, but fails to completely remove octarepeat-bound Zn(II) ions.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…By performing a systematic XAS study of a set of samples in which Cu(II) at increasing concentrations was added to tetra-octarepeat–Zn(II) complexes, we showed that the metal–peptide coordination mode depends not only, as expected, on the relative concentrations of the metals but, by comparison with the old XAS measurement of Stellato et al (2011), that the order in which the two metal ions are added to metal–tetra-octarepeat complexes is also important. Indeed, not only is Zn(II) unable to completely remove octarepeat-bound Cu(II) ions (as was already made clear by Stellato et al 2011) but, as we prove here, the opposite is also true, i.e. Cu(II) modifies the mode of Zn(II) coordination by partly displacing it, but fails to completely remove octarepeat-bound Zn(II) ions.…”
Section: Introductionmentioning
confidence: 55%
“…A parallel X-ray absorption spectroscopy (XAS) study (Stellato et al 2011) confirmed the ability of Zn(II) to modulate Cu(II) coordination, adding the important information that a single tetra-octarepeat domain can bind Cu(II) and Zn(II) ions simultaneously. Analysis of the XAS data also showed that Zn(II) competes with Cu(II) for His-binding by directly interacting with the tetra-octarepeat region, but it is unable to completely displace Cu(II).…”
Section: Introductionmentioning
confidence: 93%
“…A reduced Zn content in brains with prion disease has been revealed, 20,113 and a few other studies suggest that Zn binds to the octapeptide repeats in PrP C , albeit at an apparently lower affinity. [154][155][156] Evidence also exists that the interaction promotes the endocytosis of PrP c . 157,158 Although Spevacek et al showed that Zn binding changes the structure of murine PrP c , 159 the structural and functional consequences of Zn-prion interaction are still largely unknown.…”
Section: Role Of Other Metals In Prion Diseasementioning
confidence: 93%
“…The concentration of Zn in the brain is much higher compared to Cu; therefore, Zn 2+ may influence PrP C binding to Cu [34]. Bioinformatics analysis has revealed evolutionary similarities between prion genes and gene-encoding ZIP transporters [35,36].…”
Section: Zn and Normal Prion Proteinmentioning
confidence: 99%